Estudio de factibilidad para el montaje de una planta de producción de cerveza artesanal en la ciudad de Villavicencio-Meta - Moreno Moreno, Maibeth Melissa; Ordóñez Fuentes, Luis Guillermo (Universidad Antonio Nariño, 2021)
The feasibility for a craft beer production plant in Villavicencio-Meta seeks to determine if the project is viable. Based on this, a market research has been carried out through a survey focused on demand, where relevant information was obtained on consumption habits, preferences and information used in the distribution and sale of this type of product. For the technical evaluation, the identification of productive processes is carried out taking into account the market perspectives, related to, plant distribution, equipment, as well as the organizational structure of the plant, taking into account the payroll and functions of each position for the management of the company. In the legal evaluation, the documentary process of administrative and regulatory processes is carried out, as well as the performance of the environmental evaluation analyzing the possible environmental impacts that may occur, therefore, the environmental impact measures are carried out for the production by of the plant. Finally, in the financial evaluation, the costs evidenced in all the studies carried out previously were taken into account, as well as the financial indicators for the execution of the sensitivity analysis of this research that demonstrate the profitability of the project in the short term.